1969
DOI: 10.1021/ja01038a031
|View full text |Cite
|
Sign up to set email alerts
|

Secondary deuterium isotope effects in radical-forming reactions. IV. Concerted perester decompositions

Abstract: The secondary deuterium isotope effects on the rates of decomposition of /-butyl peresters of phenylacetic (1), hydratropic (2), , -dimethylphenylacetic (3), and pivalic acids have been determined by infrared, galvinoxyl, and double-labeling methods. The a effects for 1 and 2 are 1.03-1.06 per deuterium. The ß effects for the series are 1.014-1.020 per deuterium. The implications of these effects with respect to the detailed mechanisms of the reactions are discussed. Preliminary investigations2 of secondary de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1970
1970
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…Our results (Table 2) show that within experimental error (±3%) the two propionic acids react at the same rate (k H /k D ~1.0), suggesting that the rate of iron() porphyrin formation depends on the rate of homolytic cleavage of the iron-ligand bond [step (ii)] and not decarboxylation to give the alkyl radical. In agreement with this conclusion Koenig and Wolff 25 Further support for the photo-reaction proceeding via step (ii) rather than step (v) comes from a plot of the log k obs values for the alkylcarboxylic acid reactions against the Taft σ* constant of the alkyl group which gives a good linear correlation (r = 0.980) with a ρ* value of Ϫ6.35 ± 0.735 (Fig. 2).…”
Section: Alkylcarboxylic Acidssupporting
confidence: 59%
“…Our results (Table 2) show that within experimental error (±3%) the two propionic acids react at the same rate (k H /k D ~1.0), suggesting that the rate of iron() porphyrin formation depends on the rate of homolytic cleavage of the iron-ligand bond [step (ii)] and not decarboxylation to give the alkyl radical. In agreement with this conclusion Koenig and Wolff 25 Further support for the photo-reaction proceeding via step (ii) rather than step (v) comes from a plot of the log k obs values for the alkylcarboxylic acid reactions against the Taft σ* constant of the alkyl group which gives a good linear correlation (r = 0.980) with a ρ* value of Ϫ6.35 ± 0.735 (Fig. 2).…”
Section: Alkylcarboxylic Acidssupporting
confidence: 59%
“…It is suggested that thermal decomposition of tert -butyl peroxyesters occurs by concerted bond cleavage if a highly stable radical may be formed . The solvent viscosity dependence, secondary deuterium isotope effects, and pressure dependence of thermal decomposition rates support this assumption for a series of tert -butyl peroxyesters, such as tert -butyl diphenylperacetate, tert -butyl p -methoxyphenylperacetate, and tert -butyl p -methylphenylperacetate. However, intermediate aroyloxy radicals were observed following laser flash photolysis of, e.g., tert -butyl peroxyesters R−C(O)O−O t Bu, with R = phenyl and 9-methylfluorene …”
Section: Introductionmentioning
confidence: 96%
“…This aspect has been addressed by several groups. [6][7][8][9][10][11][12] The question about the mechanism is obviously related to the time scale of observation. On the basis of thermal experiments, concerted bond breaking and stepwise dissociation via intermediate radicals on a picosecond or nanosecond time scale cannot be safely distinguished.…”
Section: Introductionmentioning
confidence: 99%